KOMPENSASI, MOTIVASI KERJA, DAN LINGKUNGAN KERJA BERPENGARUH TERHADAP LOYALITAS KARYAWAN PADA RAME CAFÉ JIMBARAN SEAFOODia - Swadarma, I Putu Satya; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 9 No 5 (2020), 2020)
Getting loyalty from someone is not an easy job to do. Inversely proportional to the difficulty of getting it, eliminating one's loyalty actually becomes a very easy thing to do. Companies need to pay attention to factors that affect employee loyalty. The purpose of this study was to determine the effect of compensation, work motivation, and work environment on employee loyalty. The study was conducted at Rame Cafe Jimbaran Seafood. A sample of 40 employees was employed, using the saturated sample method. Data collection through questionnaires. Analysis of the data used is multiple linear regression. Compensation, work motivation, and work environment have positive effect on employee loyalty. Management should pay more attention to compensation in accordance with employee performance, high motivation, comfort in the work environment, and establish good relationships with employees with the aim of increasing employee loyalty which will have a positive impact on the company. Keywords: Compensation, Work Motivation, Work Environment, and Employee Loyalty